ASSESSMENT OF COUNTERPARTY TAXPAYERS' ACTIVITIES AND IMPROVEMENT OF TAX CONTROL MECHANISMS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article covers the theoretical issues of tax audit. The nature of the tax audit norm included in the new Tax Code of the Republic of Uzbekistan has been revealed. The experience of organizing and conducting tax audits in foreign countries is cited.